2020
DOI: 10.1080/02188791.2020.1832043
|View full text |Cite
|
Sign up to set email alerts
|

The origin and impact of an ESL teacher’s beliefs on curriculum design

Abstract: Teachers in institutions of higher education have a very high degree of freedom when designing curricula. They make decisions on learning objectives, content, content organization, teaching arrangement, and assessment. Teachers' beliefs regarding curriculum design affect decisionmaking and planning processes, teaching approaches, and their relationships with students. This study aimed to examine the role beliefs played in influencing an English as a Second Language (ESL) teacher's curriculum design. The teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The present study revealed five major themes, derived from 15 subthemes, regarding the pre-service pre-primary teachers' beliefs about teaching EFL to young learners in Macau. Generally, many previously documented beliefs themes were identified (Calderhead, 1996 ; Borg, 2003 , 2006 ; Zheng, 2009 ; Shieh and Reynolds, 2020 ). Importantly, the findings also showed several beliefs subthemes that were not previously documented in the literature by pre-service pre-primary teachers such as epistemological beliefs informed by educational literature, beliefs about generalizability/transferability of research findings, and beliefs about research engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed five major themes, derived from 15 subthemes, regarding the pre-service pre-primary teachers' beliefs about teaching EFL to young learners in Macau. Generally, many previously documented beliefs themes were identified (Calderhead, 1996 ; Borg, 2003 , 2006 ; Zheng, 2009 ; Shieh and Reynolds, 2020 ). Importantly, the findings also showed several beliefs subthemes that were not previously documented in the literature by pre-service pre-primary teachers such as epistemological beliefs informed by educational literature, beliefs about generalizability/transferability of research findings, and beliefs about research engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the relationship between curriculum development and language teacher professional identity. For example, Shieh and Reynolds's (2020) case study showed that while teachers may perceived themselves as agentive professionals, they may recognise that their personal experiences as postgraduate students can enhance their understanding of curriculum development. In a similar study, Zhu and Shu (2017) examined how a teacher's engagement with curriculum development was boosted through the mediation of teacher cognition and situated practices.…”
Section: Curriculum and Language Teacher Professional Identitymentioning
confidence: 99%
“…Currently, the pre-primary education program the pre-service teachers were enrolled in only contains a single 1.5 credit hour course that teaches about English language education. As teacher educators and teacher education training have the most influence on teachers' beliefs (Shieh & Reynolds, 2021), early childhood education programs in the Macau SAR and similar areas may need to consider increasing the number of credit hours devoted to language education.…”
Section: Beliefs About Learning To Teachmentioning
confidence: 99%
“…The impact of English language teachers’ previous L2 learning experiences on their beliefs and classroom practice has been investigated in a large body of research, particularly in the 1980s and 1990s (Borg, 2006). Language teachers’ beliefs about language learning can shape their instructional practices and influence learners’ experiences (Altan, 2012; Johnson, 1994; Mardali et al, 2019; Shieh & Reynolds, 2021). These beliefs often come from teachers’ experiences as language learners, as well as their educational background (Pusparini et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%